ISLAMIC LEGAL PRINCIPLES AND NATIONAL REFORM: A STUDY OF THE 2023 INDONESIAN PENAL CODE - Abdul Rokhim; Karimuddin Abdullah Lawang; Zuraida Zuraida; Fatahillah Muhammad Syahrul (Universitas Syiah Kuala, 2025)
This study examine the transformation of the concept of justice in Islamic criminal law as a contribution to the reform of national criminal law. The assess the extent to which the principles of justice in Islamic criminal law, such as proportional justice, victim protection, and the principle of public benefit (maslahah), have been incorporated into the new national criminal law system, particularly within the 2023 Indonesian Penal Code (KUHP). This research employs a doctrinal method through literature analysis, drawing on national legislation, jurisprudence, and both classical and contemporary Islamic legal thought. The findings reveal that although several Islamic legal principles are beginning to be accommodated, such as the application of restorative justice, a more humane sentencing approach, and the acknowledgment of local values, this integration remains partial and does not yet fully reflect the comprehensive framework of Islamic justice. Therefore, transforming the national criminal law system through the values of Islamic legal principles is a strategic step toward building a justice system that is more responsive, substantively fair, and aligned with the Indonesian national identity.